THE INFLUENCE OF RECRUITMENT, SELECTION AND COMPETENCY ON EMPLOYEE PERFORMANCE AT PT. JASAMARGA TOLLROAD OPERATOR - Yulistiyono, Agus; Gunawan, Yanthi Meytri; Saputri, Ranita (Univesitas Muhammadiyah Tangerang, 2023)
The purpose of this research is to determine the influence of recruitment, selection and employee competency on the performance of PT employees. Jasamarga Tollroad Operators. This study uses a quantitative approach. The sample in this research was 107 respondents, and the method in this research used descriptive and quantitative. Primary data collection was obtained from distributing questionnaires. The results of this research show that partially the Recruitment Variable (X1) has a significant effect on Employee Performance (Y) with a regression test result of 0.433, with a significance level of 0.003 (very significant). The Selection Variable (X2) has a significant effect on Employee Performance (Y) with a regression test result of 0.491, with a significance level of 0.000 (very significant). The Competency variable (X3) has a significant effect on Employee Performance (Y) with a regression test result of 0.238, with a significance level of 0.017 (very significant). Simultaneously, the recruitment, selection and competency variables have a significant effect on employee performance (Y) with the results of F-count 18,350 > F-table 2.69 with a sig value of 0.00 (very significant).Keywords: Recruitment, Selection, Competency and Employee Performance.